Fat-free mass using bioelectrical impedance analysis as an alternative to dual-energy x-ray absorptiometry in calculating energy availability in female adolescent athletes - Ramos, I. E.; Coelho, G. M.; Lanzillotti, H. S.; Marini, E.; Koury, J. C. (International Journal of Sport Nutrition and Exercise Metabolism, 2022)
Energy availability (EA) is calculated by subtracting exercise energy expenditure from energy intake, adjusted for fat-free mass (FFM) obtained using accurate methods, such as dual-energy X-ray absorptiometry (DXA). Unlike DXA, the bioelectrical impedance analysis (BIA) is low in cost, simple and easy to carry out. This study aimed to test the concordance between the calculation of EA using FFM values from four BIA predictive equations and FFM obtained using DXA in female adolescent athletes (n = 94), recruited via social media. Paired Student`s t test, Wilcoxon test, Lin`s concordance correlation coefficient, root mean square error, limits of agreement, and mean absolute percentage error were used to evaluate agreement between the FFM values obtained by the four SF-BIA predictive equations and DXA. Regression linear analysis was used to determine the relation between FFM values obtained using DXA and the BIA predictive equations. Standardized residuals of the FFM and EA were calculated considering DXA values as reference. The most appropriate model for the FFM (limits of agreement = 4.0/-2.6 kg, root mean square error = 1.9 kg, mean absolute percentage error = 4.34%, Lin`s concordance correlation coefficient = .926) and EA (limits of agreement = 2.51/4.4 kcal·kg FFM-1·day-1, root mean square error = 1.8 kcal·kg FFM-1·day-1, mean absolute percentage error 4.24%, Lin`s concordance correlation coefficient = .992) was the equation with sexual maturity as a variable, while the equation with the greatest age variability was the one with the lowest agreement. FFM-BIA predictive equations can be used to calculate EA of female adolescent athletes. However, the equation should be chosen considering sex, age, and maturation status. In the case of athletes, researchers should use equations developed for this group.